2006
DOI: 10.1038/sj.ijo.0803510
|View full text |Cite
|
Sign up to set email alerts
|

Association between cannabinoid type-1 receptor polymorphism and body mass index in a southern Italian population

Abstract: Context: Endocannabinoids control food intake via both central and peripheral mechanisms, and cannabinoid type-1 receptor (CB1) modulates lipogenesis in primary adipocyte cell cultures and in animal models of obesity. Objectives: We aimed to evaluate, at the population level, the frequency of a genetic polymorphism of CB1 and to study its correlation with body mass index. Design, setting and participants: Healthy subjects from a population survey carried out in southern Italy examined in 1992-1993 and older th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 13 publications
(12 reference statements)
7
45
0
1
Order By: Relevance
“…In a Belgian cohort, the CNR1 rs1049353 SNP was found to be associated with waist-to-hip ratio (WHR) in obese men (10). Likewise, in a study from Southern Italy (11), rs1049353 was linked with obesity; however, neither of these results were confirmed in studies on obese German children and adolescents (12) or mid-age American adults in the Framingham Study (13).…”
Section: Introductionmentioning
confidence: 38%
“…In a Belgian cohort, the CNR1 rs1049353 SNP was found to be associated with waist-to-hip ratio (WHR) in obese men (10). Likewise, in a study from Southern Italy (11), rs1049353 was linked with obesity; however, neither of these results were confirmed in studies on obese German children and adolescents (12) or mid-age American adults in the Framingham Study (13).…”
Section: Introductionmentioning
confidence: 38%
“…Many investigators have suggested than an association exists between various CNR1 gene polymorphisms and the parameters of obesity in various populations. [8][9][10]16,17 On the other hand, Lieb et al, 18 who studied 18 singlenucleotide polymorphisms in the CNR1 gene in 2415 Framingham Offspring Study participants, found no evidence for an association of CNR1 polymorphisms with BMI, waist circumference, or visceral or subcutaneous adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A number of genetic polymorphisms have been described in the CB 1 receptor, and their correlation with various conditions has been examined (386). Although the results are rather controversial, some of the polymorphisms have been reported to link to obesity-related phe-notypes (173,448), hebephrenic schizophrenia (78,530), childhood attention deficit/hyperactivity disorder (429), and depression in Parkinson's disease (20).…”
Section: Structurementioning
confidence: 99%